2019
DOI: 10.1007/s10389-019-01028-w
|View full text |Cite
|
Sign up to set email alerts
|

Innovative tool for health promotion for at-risk Thai people with hypertension

Abstract: Background: Hypertension is a major risk factor in heart failure, arterial aneurysms, peripheral arterial disease, chronic kidney disease, stroke and myocardial infarction. Methods: This study was an experimental study. From patients with hypertension presenting to karaj Health Center, 90 patients were selected according to the eligibility criteria and were assigned randomly to two groups, the intervention group (45 patients) and the control group (45 patients). The data were collected through questionnaires. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 19 publications
0
11
0
3
Order By: Relevance
“…[ 11 12 13 ] Like most chronic diseases, hypertension is closely associated with lifestyle, mental health, and quality of life of patients, and if it is not controlled on-time and appropriately, it will cause various diseases, significant disabilities, reduction of productivity, and ultimately reduction of the quality of people's lives. [ 14 15 16 17 18 ] The study of Ebadi et al . [ 19 ] and Shamsi et al .…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 12 13 ] Like most chronic diseases, hypertension is closely associated with lifestyle, mental health, and quality of life of patients, and if it is not controlled on-time and appropriately, it will cause various diseases, significant disabilities, reduction of productivity, and ultimately reduction of the quality of people's lives. [ 14 15 16 17 18 ] The study of Ebadi et al . [ 19 ] and Shamsi et al .…”
Section: Introductionmentioning
confidence: 99%
“…Jenis atau metode penelitian yang teridentifikasi dari artikel menunjukkan semua penelitian menggunakan pendekatan penelitian kuantitatif. Penelitian tersebut berupa quasi experimental design (9)(10)(11)(12)(13)(14)(15) , randomized control trial (16)(17)(18)(19)(20)(21)(22) , cohort study (23) , longitudinal observational study (24) , Pre-Experimental One Group Pre-test Post-test design study (25) , pre-test-post-test design (26,27) .…”
Section: Hasilunclassified
“…Edukasi yang diberikan berupa materi teoritis seperti ceramah, diskusi, konseling, e-learning, dan juga praktik seperti workshop atau training dengan berbagai topik terkait. Topik/ materi tersebut berupa fakta-fakta seputar hipertensi seperti definisi (11,15,16) , tanda dan gejala, faktor risiko (15,16) , bagaimana mendiagnosa dan penanganannya, tekanan darah normal, pencegahan hipertensi (9,15,25) , komplikasi (16,20,26) , obat (16,18,21,28,29) , efek samping obat, pentingnya minum obat secara teratur, pentingnya pemeriksaan tekanan darah secara berkala (16) , diet (12,18,29) , aktifitas fisik (18,28,29) , teknik relaksasi seperti tarik nafas dalam (10) , relaksasi otot, guided imagery (10,12) , Roy Adaptation Model yang dibuat menjadi sebuah panduan yang berisi definisi, faktor risiko, gejala, pengukuran tekanan darah di rumah (14) , pengurangan sodium (22,30) , self management untuk hipertensi, hipertensi memungkinkan terjadinya stroke, bisakah sembuh dari hipertensi, penanganan hipertensi, pentingnya mematuhi pengobatan (27) , hidup dengan hipertensi, makanan sehat (28) , modifikasi gaya hidup, mengurangi konsumsi alkohol, DASH diet (30) , kehilangan berat badan (29,30) , pengontrolan tekanan darah, keuntungan hidup sehat, efek buruk akibat hipertensi (19) , grade hipertensi (20) , pengendalian penyakit, pencegahan komplikasi tambahan, menghentikan rokok (29), Self-Blood Pressure Monitoring (SBP...…”
Section: Hasilunclassified
See 1 more Smart Citation
“…Moreover, the cost of frequent hospitalization reduces, and the hospital beds are not occupied in vain, so that the person can work as a young workforce in the family and community [12,13]. From among the models and programs used in self-management, Model 5A, known as behavior change counseling, is an evidence-based approach appropriate for behavior modification and health promotion, which has five steps: Assess, Advise, Agree, Assist, and Arrange [14,15]. Regarding this, the results of other studies have shown the effectiveness of 5A self-management program [16,17].…”
Section: Introductionmentioning
confidence: 99%